The Orthopaedic Training Study, Phase II 1968-1972. Final Report Supplement, Psychomotor Skills, Part B - Olson, Carl J.; Illinois Univ., Urbana. Medical Center ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
This document, as a supplement to the final report of the Orthopaedic Training Study, presents a discussion of the rationale behind the implementation of a laboratory course in psychomotor skills development for medical students. Medical educators examined resident training in terms of 3 components of cognitive elements of learning: cognitive, affective, and psychomotor. It was determined that development of the psychomotor aspects of orthopaedic surgery in any sequenced or ordered fashion is largely ignored. Thus, the document studies and outlines a possible laboratory course in psychomotor skills in orthopaedic surgery, a psychomotor skills plaster laboratory, and an orthopaedic traction skills laboratory. See also HE 003 277 and HE 003 276. (HS)
Sponsoring Agency: National Institutes of Health (DHEW), Bethesda, MD. Bureau of Health Professions Education and Manpower Training.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Higher Education; Laboratories; Medical Education; Medical Students; Psychomotor Skills; Skill Development; Training Laboratories